Comprehensive study on structural properties of Zn2SiO4 glass formation derived from waste rice husks - Mohamed Khaidir, Rahayu Emilia; Yap, Wing Fen; Mohd Zaid, Mohd Hafiz; Sheh Omar, Nur Alia (2018)
Combination of zinc oxide and white rice husk ash (ZnO0.60 – WRHA0.40) were prepared to produce zinc silicate glasses (Zn2SiO4) by conventional melt and quench technique at 1450 ˚C. X-Ray Fluorescent (XRF) results were being analyzed to confirm the chemical composition presents in WRHA sample. The glass behaviors were investigated using X-Ray Diffractometer (XRD). XRF shows that WRHA contains about 90% of silica dioxide (SiO2) while XRD shows that the glass amorphous nature phase was formed at composition of (ZnO0.60 – WRHA0.40). FESEM shows clear glassy surface which indicates the amorphous glass phase.